Evaluation of Physalis angulata extract on Rhipicephalus (Boophilus) Microplus tick larvae - Fantatto, Rafaela Regina; Sorrechia, Rodrigo; Januário, Ana Helena; Silva, Fabiano Guimarães; Kapp, Barbara Regina; Medeiros, Camila Baccetti; Pietro, Rosemeire Cristina Linhari Rodrigues (Brazilian Journal of Science, 2022)
The tick Rhipicephalus (Boophilus) microplus is responsible for large losses in livestock worldwide, causing a drop in meat and milk production, leather depreciation, annoyance to animals and transmission of hemoparasitosis that can lead to death. The control of this ectoparasite is currently carried out by synthetic chemical compounds, however, most with reported cases of resistance, makes it necessary to study new natural alternatives necessary. The present study aimed to evaluate the Physalis angulata extract between concentrations 100 - 12.5 mg mL-1 on R. (B.) microplus larvae by the impregnated paper patch test (IPPT). The results were promising and the concentrations of 100 and 50 mg mL-1 were the most effective, presenting 92.24% and 58.47% of larval mortality, respectively.